A Novel Composite Material for Foldable Building Envelopes - Rodonò, Gianluca; Sapienza, Vincenzo; Recca, Giuseppe; Carbone, Domenico Carmelo (Sustainability, 2019)
Contemporary research is increasingly focused on studying buildings that either interact with environmental boundaries or adapt themselves to their users’ needs. In the current literature, this kind of ability is given different names: responsivity, adaptability, smartness. These are different ways to refer to a common concept, with subtle nuances. Foldable surfaces are one of the most interesting geometries able to give responsivity to building components, but often their production is complex and expensive. The aim of this research was the creation of a novel material that can provide lightweight solutions for foldable building envelopes. This composite material can be folded and unfolded easily, like a sheet of paper, but with a higher mechanical performance. It is made with the thermoplastic elastomer SEBS (styrene–ethylene–butylene–styrene) as its matrix, as well as a fabric reinforcement. In this paper, following an introduction to this subject, the authors present the composite material’s production methods and its mechanical characterization.